Enhancing quantitative approaches for assessing community resilience. (1st May 2018) - Chuang, W.C.; Garmestani, A.; Eason, T.N.; Spanbauer, T.L.; Fried-Petersen, H.B.; Roberts, C.P.; Sundstrom, S.M.; Burnett, J.L.; Angeler, D.G.; Chaffin, B.C.; Gunderson, L.; Twidwell, D.; et al.
Abstract: Scholars from many different intellectual disciplines have attempted to measure, estimate, or quantify resilience. However, there is growing concern that lack of clarity on the operationalization of the concept will limit its application. In this paper, we discuss the theory, research development and quantitative approaches in ecological and community resilience. Upon noting the lack of methods that quantify the complexities of the linked human and natural aspects of community resilience, we identify several promising approaches within the ecological resilience tradition that may be useful in filling these gaps. Further, we discuss the challenges for consolidating these approaches into a more integrated perspective for managing social-ecological systems. Highlights: Resilience is a key strategy for assessing and managing emerging global challenges. Developing approaches for quantifying community resilience is of great importance. Research on resilience should account for scale and cross-scale interactions. We suggest approaches for quantitative assessments of community resilience.